Potentiation of mitochondrial dysfunction in tumor cells by conjugates of metabolic modulator dichloroacetate with a Pt(IV) derivative of oxaliplatin - Zajac, Juraj; Kostrhunova, Hana; Novohradsky, Vojtech; Vrana, Oldrich; Raveendran, Raji; Gibson, Dan; Kasparkova, Jana; Brabec, Viktor (Journal of inorganic biochemistry, 2016)
The molecular and cellular mechanisms of enhanced toxic effects in tumor cells of the Pt(IV) derivatives of antitumor oxaliplatin containing axial dichloroacetate (DCA) ligands were investigated. DCA ligands were chosen because DCA has shown great potential as an apoptosis sensitizer and anticancer agent reverting the Wartburg effect. In addition, DCA reverses mitochondrial changes in a wide range of cancers, promoting tumor cell apoptosis in a mitochondrial-dependent pathway. We demonstrate that (i) the transformation of oxaliplatin to its Pt(IV) derivatives containing axial DCA ligands markedly enhances toxicity in cancer cells and helps overcome inherent and acquired resistance to cisplatin and oxaliplatin; (ii) a significant fraction of the intact molecules of DCA conjugates with Pt(IV) derivative of oxaliplatin accumulates in cancer cells where it releases free DCA; (iii) mechanism of biological action of the Pt(IV) derivatives of oxaliplatin containing DCA ligands is connected with the effects of DCA released in cancer cells from the Pt(IV) prodrugs on mitochondria and metabolism of glucose; (iv) treatments with the Pt(IV) derivatives of oxaliplatin containing DCA ligands activate an autophagic response in human colorectal cancer cells; (v) the toxic effects in cancer cells of the Pt(IV) derivatives of oxaliplatin containing DCA ligands can be potentiated if cells are treated with these prodrugs in combination with 5-fluorouracil. These properties of the Pt(IV) derivatives of oxaliplatin containing DCA ligands provide opportunities for further development of new platinum-based agents with the capability of killing cancer cells resistant to conventional antitumor platinum drugs used in the clinic.
Keywords: Mitochondrial dysfunction; Mitochondria; Glucose metabolism; Cell Line, Tumor; 5-Fluorouracil; Organoplatinum Compounds; Acetates; Cancer therapy; Autophagy; acetáty; lidé; Humans; membránový potenciál mitochondrií; Platinum-dichloroacetate conjugates; Oxaliplatin; nádorové buněčné linie; organoplatinové sloučeniny; oxaliplatin; Membrane Potential, Mitochondrial; mitochondrie